Pak-Russia Relations: Exploring the New Avenues - Mr. Muhammad Sarmad Zia (CISS Insight Journal, 2018)
The relations between Pakistan and Russia are developing vis-à-vis geo-political and geo-strategic transformations in the international system. This paper seeks to study the regional and bilateral interests of both countries that influence this relationship. The convergence between the two former adversaries on counter-terrorism and narcotics control remains an integral part of their developing ties. Currently, it can be seen that military to military cooperation including defence procurement is increasing between the two states. It is important that other aspects of this relationship such as economic and technical cooperation are also being explored to build an enduring relationship. The two states have the potential to influence and improve regional and international security matrix through cooperation on counterterrorism, drug trafficking and money laundering on bilateral as well as regional forums such as the Shanghai Cooperation Organization. This would require serious efforts and a long-term commitment from both sides